Cisco Certified Support Technician (CCST) Networking Cert Prep: 4 Troubleshooting and Securing Networks. - Wallace, Kevin (linkedin.com, 2023)
Prepare for the Cisco Certified Support Technician (CCST) Networking certification with a look at the topics of the exam that relate to troubleshooting and securing networks.